Operation Strategies Based on Horizontal Competition and Service Capability Sharing under Demand Disturbance - Kun Wang; Dongsong Wu (Discrete Dynamics in Nature and Society)
The article considers the influence of demand disturbance on price, service capability, and operation mode selection of firms. Firstly, we discuss the equilibrium pricing and service capability strategy of the firm under three operation modes: price and service competition, price competition and service capability sharing, and price and service centralized making-decision. When there is demand disruption, firms determine their pricing and service capacity strategies under the three main operating models above. Finally, the comparative analysis shows that the influence of service capability in centralized decision price and service capability mode is greater than that on service capability in price competition and service capability sharing mode. The smoothness of service capability in price competition and service capability sharing mode is better than that in the centralized decision mode. And when the market price competition coefficient is moderate or the negative demand disturbance occurs, the price competition and service capability sharing mode has little influence on the profit compared with the other two modes (the profit loss is the smallest).